An improvement design of multi-function controller for high-tech shrimp farm - Cao, Bui Thu (Journal of Computer Science and Cybernetics, 2023)
Shrimp farming is one of the highest potential areas in the coastal provinces of Vietnam. The technical level of shrimp farming is developing strongly in the direction of high technology based on applying modern equipment and machinery. However, the efficiency of shrimp farming is still not high, the monitoring and control of the actuators are mainly manual. Shrimp farmers are not interested in using smart controllers for shrimp farms. In this article, the author evaluates the limitations of the current controllers and proposes a multi-function controller which is suitable for the practical requirements of high-tech shrimp farms (HTSFs) with significant functions such as soft configuration, overload protection, and engine damage warning for actuator devices. In addition, the proposed controller also allows monitoring and automatically controlling HTSFs on a mobile application.